2021
DOI: 10.1111/stul.12176
|View full text |Cite
|
Sign up to set email alerts
|

A Corpus‐based Study of Textual Metaphor in English Academic Writing

Abstract: This article conducted a corpus‐based study on the discipline distributions of two types of textual metaphor identified by He et al. (2015) and He and Wen (2017), conjunctionalization of conjunctive adverbs and zero conjunctionalization of hypotactic conjunctions. It is found that conjunctionalization of conjunctive adverbs is more prevalent in soft science texts than in hard science texts and zero conjunctionalization of hypotactic conjunctions is similarly distributed in hard science texts and in soft scienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…In this field, some previous research focused on the patterns and functions of L2 metaphor produced by L2 learners. For example, it is found that L2 learners could use various types of metaphors to achieve vividness, coherence, and persuasiveness [4][5][6][7]. Other previous studies investigated the influencing factors behind L2 metaphor production.…”
Section: Introductionmentioning
confidence: 99%
“…In this field, some previous research focused on the patterns and functions of L2 metaphor produced by L2 learners. For example, it is found that L2 learners could use various types of metaphors to achieve vividness, coherence, and persuasiveness [4][5][6][7]. Other previous studies investigated the influencing factors behind L2 metaphor production.…”
Section: Introductionmentioning
confidence: 99%